Atomic-level structural correlations across the morphotropic phase boundary of a ferroelectric solid solution: XBiMg1/2Ti1/2O3-(1-x)PbTiO3 - Datta, Kaustuv; Neder, Reinhard; Chen, Jun; Neuefeind, Joerg C.; Mihailova, Boriana (Scientific Reports, 2017)
Revelation of unequivocal structural information at the atomic level for complex systems is uniquely important for deeper and generic understanding of the structure property connections and a key challenge in materials science. Here we report an experimental study of the local structure by applying total elastic scattering and Raman scattering analyses to an important non-relaxor ferroelectric solid solution exhibiting the so-called composition-induced morphotropic phase boundary (MPB), where concomitant enhancement of physical properties have been detected. The powerful combination of static and dynamic structural probes enabled us to derive direct correspondence between the atomic-level structural correlations and reported properties. The atomic pair distribution functions obtained from the neutron total scattering experiments were analysed through big-box atom-modelling implementing reverse Monte Carlo method, from which distributions of magnitudes and directions of off-centred cationic displacements were extracted. We found that an enhanced randomness of the displacement-directions for all ferroelectrically active cations combined with a strong dynamical coupling between the A- A nd B-site cations of the perovskite structure, can explain the abrupt amplification of piezoelectric response of the system near MPB. Altogether this provides a more fundamental basis in inferring structure-property connections in similar systems including important implications in designing novel and bespoke material